2007
DOI: 10.1038/sj.onc.1210283
|View full text |Cite
|
Sign up to set email alerts
|

Dose–response transition from cell cycle arrest to apoptosis with selective degradation of Mdm2 and p21WAF1/CIP1 in response to the novel anticancer agent, aminoflavone (NSC 686288)

Abstract: Aminoflavone (AF, NSC 686288) is beginning clinical trials. It induces replication-mediated histone H2AX phosphorylation, DNA-protein crosslinks and activates p53. Here, we studied p21 CIP1/WAF1 and Mdm2 responses to AF. Although p53 stabilization and phosphorylation at serine 15 increased with dose and time of exposure, Mdm2 and p21 CIP1/WAF1 protein levels displayed a biphasic response, as they accumulated at submicromolar doses and then decreased with increasing AF. As both Mdm2 and p21 CIP1/WAF1 mRNA level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
25
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 38 publications
10
25
1
Order By: Relevance
“…This is consistent with what was determined in a recent publication reporting apoptosis induction by AF in other sensitive cancer cells. 12 The biphasic apoptotic response correlates with the biphasic response seen for DNA damage induced by AF in MDA-MB-468 cells.…”
Section: Aminoflavone Induces Apoptosis In Mda-mb-468 Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is consistent with what was determined in a recent publication reporting apoptosis induction by AF in other sensitive cancer cells. 12 The biphasic apoptotic response correlates with the biphasic response seen for DNA damage induced by AF in MDA-MB-468 cells.…”
Section: Aminoflavone Induces Apoptosis In Mda-mb-468 Cellsmentioning
confidence: 99%
“…36 Previous studies demonstrate the ability of AF to induce p21 expression in MCF-7 cells. 8,12 To determine whether p21 expression levels are altered in MDA-MB-468 cells following AF treatment, we exposed these cells at varying time points (2-18 hr) to AF (1 lM) and measured p21 protein expression using Western blotting. Data demonstrate that AF induces an increase in p21 expression within 2 hr and sustains this effect for the duration of treatment (Fig.…”
Section: Aminoflavone Induces S Phase Arrest In Mda-mb-468 Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is entering phase II trials for the treatment of breast cancer. Mechanistic studies on the cytotoxicity of AF have revealed that AF induces DNA damage associated with DNA-protein cross-link, DNA singlestrand breaks, and DNA replication-dependent DNA double-strand breaks (3,5). AF also inhibits DNA synthesis and induces S-phase arrest (3).…”
Section: Introductionmentioning
confidence: 99%